2020
DOI: 10.1021/acs.nanolett.9b05325
|View full text |Cite
|
Sign up to set email alerts
|

Spin Polarization Dynamics of Free Charge Carriers in CsPbI3 Nanocrystals

Abstract: Lead halide perovskites (LHPs) exhibit large spin–orbit coupling (SOC), leading to only twofold-degenerate valence and conduction bands and therefore allowing for efficient optical orientation. This makes them ideal materials to study charge carrier spins. With this study we elucidate the spin dynamics of photoexcited charge carriers and the underlying spin relaxation mechanisms in CsPbI3 nanocrystals by employing time-resolved differential transmission spectroscopy (DTS). We find that the photoinduced spin po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 46 publications
2
50
1
Order By: Relevance
“…For PA2, the initially stronger negative signal for σ probe originates from transition from |+1〉 to |0〉 (namely, Δ m J = −1), followed by spin relaxation to |−1〉, and then made |−1〉 to |0〉 transition happen, which eventually detected as positive signal for σ+ probe. This ultrafast exciton spin relaxation is due to exchange Coulomb interaction, that is, due to simultaneous monomolecular spin flip of the exciton's constituents, [ 47,61 ] which can be described by the Bir–Aronov–Pikus (BAP) model, [ 34,43,62 ] τnormals1NnormalpαnormalB3Δ2EBkαnormalBwhere N p denotes hole concentration, α B is exciton Bohr radius, ∆ represents the exchange coupling, and E B stands for exciton binding energy. For 2D perovskites system, the exchange coupling is relatively strong.…”
Section: Typical Study Cases and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For PA2, the initially stronger negative signal for σ probe originates from transition from |+1〉 to |0〉 (namely, Δ m J = −1), followed by spin relaxation to |−1〉, and then made |−1〉 to |0〉 transition happen, which eventually detected as positive signal for σ+ probe. This ultrafast exciton spin relaxation is due to exchange Coulomb interaction, that is, due to simultaneous monomolecular spin flip of the exciton's constituents, [ 47,61 ] which can be described by the Bir–Aronov–Pikus (BAP) model, [ 34,43,62 ] τnormals1NnormalpαnormalB3Δ2EBkαnormalBwhere N p denotes hole concentration, α B is exciton Bohr radius, ∆ represents the exchange coupling, and E B stands for exciton binding energy. For 2D perovskites system, the exchange coupling is relatively strong.…”
Section: Typical Study Cases and Discussionmentioning
confidence: 99%
“…Strohmair et al. [ 43 ] observed that the spin relaxation times of CsPbI 3 nanocrystals (cubic morphology, average edge length of 13 ± 3 nm) at cryogenic temperatures (32 ps) increase more than 1 order of magnitude compared with that at room temperature (3 ps), predominantly due to carrier‐longitudinal optical (LO) phonon scattering via E–Y mechanism. With further deceasing the dimension of perovskites down to QDs level, the spin relaxation dynamics show strong dependence on size and component, and the predominant E–Y mechanism in bulk perovskites is not applicable for QDs.…”
Section: Typical Study Cases and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28,29 However consensus is growing that in QC MLHP NCs the conduction and valence band edges consist of a single level significantly isolated in energy space which is only spin degenerate. 30,31 In such a scenario expectations are for a symmetric state filling effect from both bands, with a linear increase of the BE bleach for the first 2 excitons, transforming the sample from absorption to stimulated emission of the same intensity. Together with the unusual appearance of A2, these observations demonstrate that much still remains to be understood concerning electronic structure of QC MLHP NCs.…”
Section: Introductionmentioning
confidence: 99%
“…[159,166] Leveraging this excitonic structure, many studies reported the successful injection of spin-polarized excitons and carriers into perovskite NCs for a wide variety of sizes and compositions. [159,[167][168][169] Analogously to bulk HPs, spin lifetimes in NCs were reported to be in the ps-regime (see Figure 4d).…”
Section: Injection and Dynamicsmentioning
confidence: 99%